2016
DOI: 10.1016/j.amepre.2015.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Minority Health and Health Risk Factors

Abstract: Introduction Although population studies have documented the poorer health outcomes of sexual minorities, few have taken an intersectionality approach to examine how sexual orientation, gender, and race jointly affect these outcomes. Moreover, little is known about how behavioral risks and healthcare access contribute to health disparities by sexual, gender, and racial identities. Methods Using ordered and binary logistic regression models in 2015, data from the 2013 and 2014 National Health Interview Survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(58 citation statements)
references
References 35 publications
2
56
0
Order By: Relevance
“…Also, as others have observed (Austin et al, 2016; Björkenstam et al, 2016; Boehmer et al, 2014; Cochran & Mays, 2007; Fredriksen-Goldsen et al, 2013; Gonzales & Henning-Smith, 2015; Hsieh & Ruther, 2016; Siordia, 2015), LGB respondents in the NHIS evidenced higher prevalence of functional limitations and disability than did heterosexual respondents. Capitalizing on NHIS’s extensive measurement of limitations and disability, we were also able to extend these findings by showing that much of the health disadvantages in mobility, independence, and social engagement that LGB individuals reported were associated with MHSA-related factors.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Also, as others have observed (Austin et al, 2016; Björkenstam et al, 2016; Boehmer et al, 2014; Cochran & Mays, 2007; Fredriksen-Goldsen et al, 2013; Gonzales & Henning-Smith, 2015; Hsieh & Ruther, 2016; Siordia, 2015), LGB respondents in the NHIS evidenced higher prevalence of functional limitations and disability than did heterosexual respondents. Capitalizing on NHIS’s extensive measurement of limitations and disability, we were also able to extend these findings by showing that much of the health disadvantages in mobility, independence, and social engagement that LGB individuals reported were associated with MHSA-related factors.…”
Section: Discussionsupporting
confidence: 71%
“…Studies have found that LGB individuals, especially women, are more likely than heterosexual women and men to report a health disability (Austin et al, 2016; Boehmer et al, 2014; Cochran & Mays, 2007; Fredriksen-Goldsen et al, 2013; Frisch & Simonsen, 2013; Hsieh & Ruther, 2016). However, these studies did not assess the nature or extent of that disability.…”
mentioning
confidence: 99%
“…Multiple population-based studies have documented the prevalence of sexual minority identity and behavior among U.S. adults using these metrics (Chandra, Mosher, Copen, & Sionean, 2011;Copen, Chandra, & Febo-Vazquez, 2016;Farley, Stephens, Harvey, Sikes, & Wenger, 1992;Hsieh & Ruther, 2016). However, few of these studies have examined changes in the prevalence of sexual minority status over time using more than one dimension of sexual orientation or assessed if these trends vary among demographic groups (Chandra et al, 2011;Copen et al, 2016;Patterson et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Resources such as personal coping and group solidarity may counteract minority stress and help explain findings in which multiple marginalized statuses do not necessarily lead to poorer mental and physical health outcomes. Previous studies tout the consideration of both risk and protective factors in health disparities research as the minority stress model may be overly simplistic [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%